2018
DOI: 10.1126/scirobotics.aar8580
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired living structural color hydrogels

Abstract: Structural color materials from existing natural organisms have been widely studied to enable artificial manufacture. Variable iridescence has attracted particular interest because of the displays of various brilliant examples. Existing synthetic, variable, structural color materials require external stimuli to provide changing displays, despite autonomous regulation being widespread among natural organisms, and therefore suffer from inherent limitations. Inspired by the structural color regulation mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
393
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 494 publications
(397 citation statements)
references
References 48 publications
1
393
0
3
Order By: Relevance
“…[111] As these stimuli greatly overlap with the ones for actuating soft materials,one promising path in research is to combine the photonic materials with soft actuators for adaptive,d ynamic displays in future biohybrid robots (Figure 2c). [112] Directly embedding artificial "chromatophores" into the elastomeric substrates is more widely adopted in conventional soft robotic systems.T hese chromatophores are based upon materials and structures that are capable of emitting light. Examples include the patterning of microfluidic networks filled with pigmented or fluorescent liquids and overlaying highly stretchable electroluminescent polymer composites ( Figure 2d).…”
Section: Soft Display and Camouflage Materialsmentioning
confidence: 99%
“…[111] As these stimuli greatly overlap with the ones for actuating soft materials,one promising path in research is to combine the photonic materials with soft actuators for adaptive,d ynamic displays in future biohybrid robots (Figure 2c). [112] Directly embedding artificial "chromatophores" into the elastomeric substrates is more widely adopted in conventional soft robotic systems.T hese chromatophores are based upon materials and structures that are capable of emitting light. Examples include the patterning of microfluidic networks filled with pigmented or fluorescent liquids and overlaying highly stretchable electroluminescent polymer composites ( Figure 2d).…”
Section: Soft Display and Camouflage Materialsmentioning
confidence: 99%
“…[1][2][3][4][5][6] For instance, cephalopods (squid, cuttlefish, www.advmatinterfaces.de strain sensors, such as incapability of information delivery, [35] humidity dependence, [19,22,25] and lack of scalability [15,23] and has various potential applications including stress, strain and bending sensors, data encryption and security labels. [1][2][3][4][5][6] For instance, cephalopods (squid, cuttlefish, www.advmatinterfaces.de strain sensors, such as incapability of information delivery, [35] humidity dependence, [19,22,25] and lack of scalability [15,23] and has various potential applications including stress, strain and bending sensors, data encryption and security labels.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the culture time, the aligned cells increased from 39 ± 5% after 8 h of seeding to 57 ± 3% after 72 h, and then decreased after 192 h as a result of the formation of confluence. In another study, Fu et al fabricated 20, 40, and 60 µm wide parallel grooves on gelMA hydrogel films by replicating the patterns on silicon wafers . It was found that 55% of CMs aligned within 30° from the direction of 60 µm grooves, while this proportion increased when the width decreased (80% for 20 µm).…”
Section: Nano‐ and Microfabrication For Cell Alignmentmentioning
confidence: 99%